Factors Associated with Fertility Intention among Women during the COVID-19 Pandemic in Government Hospitals of Kaski District, Nepal - Aryal, Vijay (Prithvi Journal of Research and Innovation, 2022)
COVID-19 has affected the reproductive health of women worldwide. Such effects were mainly on the reduction in child-birth, postponement of fertility plans and loss of lives of mothers and children as well as still births. The paper attempts to examine the factors associated with the impact of the pandemic on fertility intentions of women who are preparing to have a child even if they already had one or more children. Patient exit survey during 9 June 2022 to 8 July 2022 was conducted at selected hospitals among women who have visited an Obstetric and Gynaecological specialist at the Out Patient Department for consultation. Among 138 participant women who provided with oral informed consent to participate, 34 were infected with severe acute respiratory syndrome coronavirus-2 (SARS-COV-2). The number of living children, gender of the children and the educational attainment of the mothers have been found to be significantly associated with change in fertility intention of women. A qualitative study is necessary to ascertain on why the number and gender of children is central to changes in fertility intentions at the times of the pandemic as such.